BO’LAJAK TEXNOLOGIK TA’LIMI O’QITUVCHILARNING KASBIY KOMPETENSIYALARNI MILLIY QADRIYATLAR ASOSIDA RIVOJLANTIRISH METODIKASI - Kutlimuradov, K.A. (SCIENCE and SOCIETY, 2024)
In the article, the methodology of developing professional competencies of future teachers based on national values, connecting the working activities of "Eminbar.uz" technology with the database, in the performance of independent tasks of future technological education teachers, professional skills related to folk crafts issues of openness, fairness and transparency are ensured in the development of competences based on national values and in the evaluation of their knowledge.
Keywords: "Eminbar.uz" in the teaching of "Folk crafts and artistic design" subject "Tools and materials used in wood carving" folk crafts professional competencies national values